2016
DOI: 10.11604/pamj.2016.25.67.7758
|View full text |Cite
|
Sign up to set email alerts
|

Prévalence des dyslipidémies au laboratoire de biochimie du CHU Aristide le Dantec de Dakar, Sénégal

Abstract: IntroductionL'objectif de cette étude était d'évaluer la prévalence des dyslipidémies chez les patients reçus au laboratoire de Biochimie de l'Hôpital Aristide Le Dantec pour le dosage d'un paramètre lipidique au cours de l'année 2013.MéthodesIl s'agit d'une étude rétrospective portant sur 1356 patients âgés de 10 à 94 ans reçus au laboratoire de Biochimie du CHU Le Dantec de janvier à décembre 2013. Etaient inclus dans l'étude, tous les patients ayant au moins un paramètre du bilan lipidique dont les résultat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…This was also noted in a population of the same ethnic group in Benin [18]. The hypercholesterolemia rate of 1.9% was much lower than that found at the Saint Louis University Hospital in Senegal which was 60.9% [5] and that found at the Aristide Le Dantec Hospital in Dakar which was 30.9% [4]. This difference in results is explained by the difference in methodology and the types of population survey compared to hospital surveys.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This was also noted in a population of the same ethnic group in Benin [18]. The hypercholesterolemia rate of 1.9% was much lower than that found at the Saint Louis University Hospital in Senegal which was 60.9% [5] and that found at the Aristide Le Dantec Hospital in Dakar which was 30.9% [4]. This difference in results is explained by the difference in methodology and the types of population survey compared to hospital surveys.…”
Section: Discussionmentioning
confidence: 69%
“…However, despite the frequency of cardiovascular diseases, data on the prevalence of risk factors such as hypertension and dyslipidemia are rare. Only a few epidemiological surveys have been carried out in hospitals in the city of St Louis [3], and Dakar and in rural areas reporting dyslipidemia values ranging from 39.3% to 80% [4][5][6]. The STEPS study in 2015 reported a prevalence of 13.3% of hypertension and 10.1% of hypercholesterolemia among adults in Senegal [7].…”
Section: Introductionmentioning
confidence: 99%
“…to those reported in Chad [17]. In contrast, 0.51% hypertriglyceridemia was found in Senegal [15] and 16.51% in Côte d'Ivoire [16]. On the one hand, these disparate data may be linked to the socio-demographic characteristics of the different populations studied.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, 49.19% of hypo-HDL cholesterolemia and 57.50% of hyper-LDL cholesterolemia were reported. Compared with other African studies [15] [16]…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation